The caliph and the heretic : Ibn Saba and the origins of Shiism - Anthony, Sean W. (Islamic History and Civilization, 2012)
This book is an examination of the traditions and legends concerning early Islam's first and most infamous heretic, the Yemenite Jew known as ʿAbd Allāh ibn Sabaʾ. Tracing the evolution and transformation of the many stories and narratives about Ibn Sabaʾ as adapted by Sunnī and Shīʿī scholars alike, this work attempts for the first time to give a comprehensive account of the formation of the image of Ibn Sabaʾ as the quintessential heretic of Islam's early years. It also offers a new interpretation of the historical importance and beliefs of Ibn Sabaʾ and those early Shīʿa reviled as his followers, the Sabaʾīya. The end result is a revolutionary, new portrait of Shīʿite origins and early Islamic sectarianism.